The church as a social enterprise: A strategy for economic development - Mabwe, Linda; Dimingu, Caroline; Siyawamwaya, Fairchild (International Journal of Scientific Research and Management (IJSRM), 2018)
This article aims at establishing the role played by the church in sustainable development of Zimbabwe during a period of prolonged economic meltdown.  It compares and contrasts the role of the missionaries’ church and the modern day church in Africa and whether the church has not deviated from its main reason of existence. The study recognises the role the church is playing in today’s economy and how the society and governments can optimise on its influence in various sectors. The article adopted the framework that was established by the European Economic and Social Committee in defining a social enterprise in their research on EESC recommendations on Social Enterprises (European Union: European Economic and Social Committee, 2014). A descriptive research design approach was used and both mainline and Pentecostal churches were used to draw on the conclusions. This research design heavily relied on secondary data gathered through literature review. The study concludes that churches are playing a significant role in developing the soicieties in which they are established hence contributing towards economic development. The study recommends the need for churches to identify areas of importance  in the economy, such as the manufacturing industry, so that they channel resources towards establishing enterprises that improve the nation’s Gross Domestic Product. Furthermore, the Zimbabwean government should provide special incentives for church run establishments to promote their operations. The study did not cover all churches hence the findings must be viewed in context and the conclusions were derived from the evidence gathered.